Inflammatory microenvironment in gastric premalignant lesions: implication and application - Zhang, Shengxiong; Shen, Yang; Liu, Hao; Zhu, Di; Fang, Jiansong; Pan, Huafeng; Liu, Wei (Frontiers in Immunology, 2023)
Gastric precancerous lesions (GPL) are a major health concern worldwide due to their potential to progress to gastric cancer (GC). Understanding the mechanism underlying the transformation from GPL to GC can provide a fresh insight for the early detection of GC. Although chronic inflammation is prevalent in the GPL, how the inflammatory microenvironment monitored the progression of GPL-to-GC are still elusive.Inflammation has been recognized as a key player in the progression of GPL. This review aims to provide an overview of the inflammatory microenvironment in GPL and its implications for disease progression and potential therapeutic applications. We discuss the involvement of inflammation in the progression of GPL, highlighting Helicobacter pylori (H. pylori) as a mediator for inflammatory microenvironment and a key driver to GC progression. We explore the role of immune cells in mediating the progression of GPL, and focus on the regulation of inflammatory molecules in this disease. Furthermore, we discuss the potential of targeting inflammatory pathways for GPL. There are currently no specific drugs for GPL treatment, but traditional Chinese Medicine (TCM) and natural antioxidants, known as antioxidant and antiinflammatory properties, exhibit promising effects in suppressing or reversing the progression of GPL. Finally, the challenges and future perspectives in the field are proposed. Overall, this review highlights the central role of the inflammatory microenvironment in the progression of GPL, paving the way for innovative therapeutic approaches in the future.